Blockchain Technology Model on Virtual Museum as an Effort to Enchance Balinese Cultural Metaverse - Sudipa, I Gede Iwan; Aditama, Putu Wirayudi; Yanti, Christina Purnama (Malikussaleh University, Aceh, Indonesia, 2025)
The preservation of cultural heritage in the digital era faces numerous challenges, particularly in securing authenticity, ownership, and preventing damage or loss of digital assets. This study explores the implementation of blockchain technology within a virtual museum dedicated to Balinese culture as part of the broader metaverse environment. Blockchain provides a decentralized and immutable system to record and manage digital cultural assets, ensuring transparency and security in their provenance and ownership. This paper presents a blockchain model for a virtual museum that includes features such as digital tokens and smart contracts, enabling automated processes such as the lending, licensing, and sale of digital artifacts. The integration of this model with metaverse technology creates an interactive and immersive environment for users to explore Balinese culture virtually, while simultaneously ensuring the preservation of its digital representations. The model is developed using the Rapid Application Development (RAD) methodology, enabling quick prototyping and system adjustments based on user requirements. Testing results demonstrate the system's functional success in terms of blockchain transactions and user interaction in the virtual environment. Despite challenges such as regulatory and infrastructural constraints, the findings indicate that the blockchain model has strong potential for application in digital heritage preservation. This study concludes by highlighting the benefits of blockchain in securing cultural assets and its role in promoting the Balinese digital economy through cultural tourism and virtual experiences.